Composite material and preparation method thereof, light-emitting device and display device

By connecting negative electrical organic groups on the surface of the N -type metal oxide and mixed with first metal oxides to form a composite material, the problem of film -formability of N -type semiconductor material has been solved, and better electronic injection performance and Performance of luminous devices.

CN119384208APending Publication Date: 2025-01-28TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310935407.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

N-type semiconductor materials have poor film formation in applications, which limits their applications in electron transport and injection.

Method used

By connecting a negative organic group on the surface of the N -type metal oxide, it is mixed with first metal oxides to form composite materials. The preparation method of this composite material includes lighting treatment in the mixture of the N -type metal oxide and the organic first metal salt to generate composite materials that improve the film formation and electronic injection performance.

Benefits of technology

The film formability and electronic injection performance of the composite material have been significantly improved, solving the problem of poor membrane formation of N -type semiconductor materials, while improving the overall performance of the luminous devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384208A_ABST
    Figure CN119384208A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a light-emitting device and a display device. The composite material comprises an n-type metal oxide doped with a first metal oxide, the surface of the n-type metal oxide is connected with an organic group with electronegativity, and the organic group is in coordination connection with the surface of the n-type metal oxide. The dispersibility of the n-type metal oxide can be improved, the film-forming property of the composite material can be improved, and the electron injection performance of the composite material can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optoelectronic technology, and in particular to a composite material and a preparation method thereof, a light-emitting device and a display device. Background Art

[0002] There are two types of carriers in semiconductor materials, holes in the valence band and electrons in the conduction band. According to the difference in the concentration of electrons and holes in semiconductor materials, they are divided into N-type semiconductor materials and P-type semiconductor materials. Among them, N-type semiconductor materials are also called electron-type semiconductors, which are impurity semiconductors with a free electron concentration much greater than the hole concentration. P-type semiconductor materials are also called hole-type semiconductors, which are semiconductors that mainly conduct electricity with positively charged holes, or impurity semiconductors with a hole concentration much greater than the free electron concentration.

[0003] N-type semiconductor materials are widely used as electron transport and injection materials due to their good electron injection performance, but their poor film-forming properties restrict their application to a certain extent. Summary of the invention

[0004] In view of this, the present application provides a composite material and a preparation method thereof, a light-emitting device and a display device, aiming to improve film-forming properties while making the composite material have better electron injection performance.

[0005] The embodiment of the present application is implemented as follows:

[0006] In a first aspect, a composite material is provided, comprising an n-type metal oxide doped with a first metal oxide, wherein a negatively charged organic group is connected to the surface of the n-type metal oxide, wherein the organic group comprises one or more of the following structures:

[0007]

[0008] Among them, R 1 , R 3 , R 4 A combination of one or more independently selected from H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0009] R 2 , R 5A combination of one or more selected from H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0010] The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, and C3-C10 cycloalkyl;

[0011] n is an integer of 0-4, and m is an integer of 0-6.

[0012] In a second aspect, an embodiment of the present application further provides a method for preparing a composite material, comprising: providing a first mixture, wherein the first mixture comprises an n-type metal oxide and a first solvent, wherein the first solvent comprises a hole sacrificial agent;

[0013] After the first mixture is subjected to a first light irradiation treatment, an organic first metal salt is added to the first mixture, and the first mixture is subjected to a second light irradiation treatment to obtain a composite material.

[0014] In a third aspect, an embodiment of the present application further provides a light-emitting device, comprising: a first electrode and a second electrode arranged opposite to each other; a light-emitting layer arranged between the first electrode and the second electrode; an electronic functional layer arranged between the second electrode and the light-emitting layer; wherein the material of the electronic functional layer comprises the composite material as described above, or comprises a composite material obtained by the preparation method of the composite material as described above.

[0015] In a fourth aspect, an embodiment of the present application further provides a display device, comprising a light-emitting device as described above, or comprising a light-emitting device prepared by the above-mentioned preparation method.

[0016] The composite material of the present application comprises an n-type metal oxide doped with a first metal oxide, wherein the surface of the n-type metal oxide is connected with a negatively charged organic group, and the organic group can combine with a large number of oxygen defects on the surface of the n-type metal oxide, thereby increasing the dispersibility of the n-type metal oxide, improving the film-forming property of the composite material, and further improving the electron injection performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a composite material provided in the present application;

[0019] Figure 2 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application;

[0020] Figure 3 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;

[0021] Figure 4 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;

[0022] Figure 5 EQE-J curves of device examples 1-11 and device comparative examples 1-2;

[0023] Figure 6 The external quantum efficiency stability curves of device embodiments 2 and 4 and device comparative example 1;

[0024] Figure 7 JV curves of single electron devices corresponding to device embodiments 1-11 and device comparative examples 1-2;

[0025] Figure 8 1-1 is an operating voltage curve of a single electron device corresponding to device embodiments 1-11 and device comparative examples 1-2;

[0026] Fig. 9 and Fig.10 AFM images of the electron transport layer in device comparative example 1 and device embodiment 2 respectively;

[0027] Fig.11 and Fig.12 The hydrated particle size distribution diagrams of the composite materials corresponding to Example 1 and Example 2, respectively;

[0028] Fig.13 and Fig.14 Conduction band position diagrams of zinc oxide and cobalt oxide, respectively.

[0029] Reference numerals: light emitting device 100 ; first electrode 10 ; second electrode 20 ; light emitting layer 30 ; electron functional layer 40 , electron injection layer 41 , electron transport layer 42 ; hole functional layer 50 , hole injection layer 51 , hole transport layer 52 . DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0031] In the present application, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In the present application, "at least one" refers to one or more, and "plurality" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc or abc, where a, b, c can be single or multiple, respectively.

[0032] In the present application, "substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted and no additional definition is provided, "substituted" means that the hydrogen of the compound or group is replaced by the following substituents: deuterium atoms, halogens, hydroxyls, nitro groups, cyano groups, isocyano groups, amino groups, carboxyl groups, sulfonic acid groups or their salts, phosphoric acid groups or their salts, C1-C10 alkyl groups or their combinations, etc. In the present application, aryl, aromatic groups, aromatics, and aromatic ring systems have the same meaning and can be interchanged. In the present application, heteroaryl, heteroaromatic groups, heteroaromatics, and heteroaromatic ring systems have the same meaning and can be interchanged.

[0033] In the present application, "ring atoms" means the number of atoms of the ring atoms constituting the ring itself in a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) formed by atoms bonding to form a ring, i.e., the number of atoms forming the ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The same is true for the "ring atoms" described below, unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a thienyl group is 5.

[0034] In the present application, "aryl" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom, which can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. For example, "substituted or unsubstituted aromatic groups having 6 to 30 ring atoms" refers to aromatic groups containing 6 to 30 ring atoms, and the aromatic group can be optionally further substituted. Preferably, substituted or unsubstituted aromatic groups having 6 to 24 ring atoms are used, more preferably substituted or unsubstituted aromatic groups having 6 to 18 ring atoms are used, and particularly preferably substituted or unsubstituted aromatic groups having 6 to 14 ring atoms are used, and the aromatic group can be optionally further substituted; suitable examples include, but are not limited to, phenyl, biphenyl, terphenyl, naphthyl, anthracenyl, phenanthrenyl, fluoranthenyl, triphenylene, pyrenyl, perylene, naphthyl, fluorenyl, dinaphthylenyl, acenaphthene and derivatives thereof. It is understandable that multiple aromatic groups may also be interrupted by short non-aromatic units (e.g. <10% non-H atoms, such as C, N or O atoms), specifically acenaphthene, fluorene, or 9,9-diarylfluorene, triarylamine, diaryl ether systems should also be included in the definition of aromatic groups.

[0035] In the present application, "heteroaryl or heteroaromatic group" means that at least one carbon atom on the basis of an aromatic group is replaced by a non-carbon atom, and the non-carbon atom may be an N atom, an O atom, an S atom, a Si atom, a P atom, etc. For example, "substituted or unsubstituted heteroaryl having 5 to 30 ring atoms" refers to a heteroaryl having 5 to 30 ring atoms, preferably a substituted or unsubstituted heteroaryl having 5 to 24 ring atoms, more preferably a substituted or unsubstituted heteroaryl having 5 to 18 ring atoms, and particularly preferably a substituted or unsubstituted heteroaryl having 5 to 14 ring atoms, and the heteroaryl is optionally further substituted; suitable examples include, but are not limited to, thienyl, furanyl, pyrrolyl, oxadiazolyl, triazolyl, imidazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, acridinyl, pyridazinyl, pyrazinyl, quinolyl, isoquinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, benzothienyl, benzofuranyl, indolyl, carbazolyl and derivatives thereof.

[0036] In the present application, "chain alkyl" may represent a straight chain or a chain alkyl having a branch. The carbon number of the alkyl group may be 1 to 30, 1 to 20, 1 to 10 or 1 to 6. A phrase containing the term, for example, "chain alkyl of C1 to C30" refers to a chain alkyl group containing 1 to 30 carbon atoms, each occurrence of which may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, and C30 alkyl. Non-limiting examples of chain alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylpentyl, and the like.

[0037] In the present application, "cycloalkyl" means a cyclic alkyl group, "C3-C30 cycloalkyl" means a cycloalkyl group containing 3-30 carbon atoms, and each occurrence can be independently C3 cycloalkyl, C4 cycloalkyl, C5 cycloalkyl, C6 cycloalkyl, C7 cycloalkyl, and up to C30 cycloalkyl. Non-limiting examples of cycloalkyl groups include cyclopentyl, cyclohexyl, 4-methylcyclohexyl, 4-tert-butylcyclohexyl, cyclooctyl, etc. In the present application, "alkenyl" means a chain olefin, "C2-C30 alkenyl" means an alkenyl group containing 2-30 carbon atoms, and non-limiting examples of alkenyl groups include ethenyl, propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, etc. In the present application, "cycloalkenyl" refers to a cyclic olefin, and "C3-C30 cycloalkenyl" refers to a cycloalkenyl containing 3 to 30 carbon atoms. Non-limiting examples of cycloalkenyl include cyclopentene, cyclohexene, 4-methylcyclohexene, 4-tert-butylcyclohexene, and the like.

[0038] In the present application, "alkynyl" means chain alkynes, "C2-C30 alkynyl" means alkynyl containing 2-30 carbon atoms, and non-limiting examples of alkynyl include ethynyl, propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, etc. In the present application, "cycloalkynyl" means cyclic alkynes, and "C6-C30 cycloalkynyl" means cycloalkynyl containing 6-30 carbon atoms, and non-limiting examples of cycloalkynyl include cyclohexyne, cycloheptyne, cyclooctyne, etc.

[0039] In the present application, "alkoxy" refers to a group with the structure "-O-alkyl", that is, a chain alkyl or cycloalkyl group as defined above connected to other groups via an oxygen atom. "C1-C30 alkoxy" refers to an alkoxy group with an alkyl group of 1 to 30 carbon atoms connected to an oxygen atom. Phrases containing this term include, but are not limited to, methoxy (-O-CH 3 or -OMe), ethoxy (-O-CH 2 CH 3 or -OEt) and tert-butyloxy (-OC(CH 3 ) 3 or -OtBu). In the present application, "alkoxycarbonyl" refers to a carbonyl substituted with an alkoxy group, and "C1-C10 alkoxycarbonyl" refers to a carbonyl substituted with an alkoxy group with a C1-C10 alkoxy group, wherein the alkoxy group is as defined above. Suitable examples of phrases containing this term include, but are not limited to, methoxycarbonyl (-CO-OCH 3 ), ethoxycarbonyl (-CO-OCH 2 CH 3 ) and tert-butyloxycarbonyl (-CO-OC(CH 3 ) 3 In the present application, "alkylthio" refers to a group with the structure "-S-alkyl", that is, a chain alkyl or cycloalkyl as defined above connected to other groups via a sulfur atom. Phrases containing this term include, but are not limited to, methylthio (-S-CH 3 or -SMe), ethylthio (-S-CH 2 CH 3 or -S-Et) and tert-butylthio (-SC(CH 3 ) 3 or -S-tBu).

[0040] The present application provides a composite material, comprising an n-type metal oxide doped with a first metal oxide, wherein a surface of the n-type metal oxide is connected with a negatively charged organic group.

[0041] In one embodiment, the organic group includes one or more of the following structures:

[0042]

[0043] Among them, R 1 , R 3 , R 4 A combination of one or more independently selected from H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0044] R 2 , R 5 A combination of one or more selected from H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms;

[0045] The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, C3-C10 cycloalkyl; n is an integer of 0-4, and m is an integer of 0-6.

[0046] In this embodiment, the organic group is coordinated and connected to the surface of the n-type metal oxide, which can react with a large number of oxygen defects (such as VOs, Ov, V O The combination of the above-mentioned composite material and the n-type metal oxide can increase the dispersibility of the n-type metal oxide and improve the film-forming property of the composite material; on the other hand, the electron injection performance of the composite material can be further improved.

[0047] In one embodiment, the conduction band energy level of the first metal oxide is 0.2 to 0.4 eV lower than the conduction band energy level of the n-type metal oxide. The conduction band energy level of the first metal oxide is 0.2 to 0.4 eV lower than the conduction band energy level of the n-type metal oxide, thereby reducing the electron injection barrier and improving the electron injection and transport performance of the composite material.

[0048] In one embodiment, n is selected from any integer of 0, 1, 2, 3 and 4, and m is selected from any integer of 0, 1, 2, 3, 4, 5 and 6. In one embodiment, n is selected from 0 or 1. In one embodiment, m is selected from 0.

[0049] In one embodiment, R 1 , R 2 , R 3 , R 4 , R 5 Each occurrence is independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C10 alkyl, substituted or unsubstituted C3-C10 cycloalkyl, substituted or unsubstituted C2-C10 alkenyl, substituted or unsubstituted C3-C10 cycloalkenyl, substituted or unsubstituted aryl with 6-12 ring atoms, substituted or unsubstituted heteroaryl with 5-12 ring atoms. In one embodiment, the substituent is selected from one or more combinations of C1-C10 alkoxycarbonyl, C1-C10 alkyl, and C3-C10 cycloalkyl.

[0050] In one embodiment, R 1 , R 3 , R 4 Each occurrence is independently selected from H, one or more of the following structures:

[0051]

[0052] Among them, R 6 Each occurrence is selected from one or more of H, D, and C1-C10 alkyl; n1 is an integer from 0 to 4, and n2 is an integer from 0 to 10; R 7 Each occurrence is selected from H, D, C1-C10 alkyl, -C(=O)-(CH 2 ) m5 -CH 3 One or more of , m1 is an integer of 0 to 5, m2 is an integer of 0 to 7, m3 is an integer of 0 to 4, and m5 is an integer of 0 to 5.

[0053] Furthermore, the organic group may include one or more of the following structural formulas:

[0054]

[0055]

[0056] The above-mentioned electronegative organic group can be coordinated and connected to the surface of the n-type metal oxide, so that it can combine with a large number of oxygen defects on the surface of the n-type metal oxide, increase the dispersibility of the n-type metal oxide, improve the film-forming property of the composite material, and enhance the electron injection performance of the composite material.

[0057] In this embodiment, the n-type metal oxide belongs to an n-type semiconductor material, which is a semiconductor material that is mainly electronically conductive. That is, there are two types of carriers in the n-type metal oxide, namely, holes in the valence band and electrons in the conduction band, but electronic conductivity is the main one.

[0058] In one embodiment, the n-type metal oxide includes a doped or undoped second metal oxide, the undoped second metal oxide includes one or more of zinc oxide, titanium dioxide, tin dioxide, and aluminum oxide, the doped second metal oxide includes the undoped second metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y.

[0059] In one embodiment, the molar ratio of the doping element to the second metal oxide may be (0.05-5):100, specifically (0.05-1):100, (1-2):100, (2-3):100, (3-4):100, (4-5):100, etc. In one specific embodiment, the n-type metal oxide is selected from zinc oxide. In another specific embodiment, the n-type metal oxide is selected from Mg-doped zinc oxide (ZMO).

[0060] The conduction band energy level of the first metal oxide is 0.2 to 0.4 eV lower than that of the n-type metal oxide, that is, the first metal oxide with a relatively low conduction band energy level is doped into the composite material mainly composed of the n-type metal oxide, and the first metal oxide is 0.2 to 0.4 eV lower than the conduction band energy level of the n-type metal oxide, so that the composite material includes a gradually decreasing conduction band energy level, that is, a gradient conduction band energy level, thereby reducing the electron injection barrier and improving electron injection.

[0061] In one embodiment, the first metal oxide includes one or more of cobalt oxide and molybdenum oxide.

[0062] In a specific embodiment, the n-type metal oxide is selected from zinc oxide, and the first metal oxide is selected from cobalt oxide. In this specific embodiment, in the cobalt oxide-doped zinc oxide, Co 2+ Radius (0.068nm) and Zn 2+ The radius (0.072nm) is similar, so Co 2+It is easy to fill Zn vacancies on the surface of zinc oxide, thereby reducing defects in zinc oxide nanoparticles, improving the performance of the composite material, and making the cobalt oxide and zinc oxide more effectively combined, thereby effectively improving the electron injection performance of the composite material.

[0063] In one embodiment, the average particle size of the n-type metal oxide is in the range of 2 to 10 nm, specifically 4 nm, 6 nm, 8 nm, etc. In one embodiment, the mass ratio of the first metal oxide to the n-type metal oxide is (3 to 10):100, specifically (3 to 9):100, (4 to 9):100, (4 to 8):100, (5 to 8):100, (5 to 7):100, (6 to 7):100, etc. The mass ratio can reduce the electron injection barrier, improve the electron injection and transport properties of the composite material, and improve the film forming property.

[0064] The present application also provides a method for preparing a composite material, see Figure 1 , Figure 1 It is a flow chart of an embodiment of a method for preparing a composite material provided in the present application, which specifically includes the following steps: Step S11: providing a first mixture, wherein the first mixture includes an n-type metal oxide and a first solvent; Step S12: after the first mixture is subjected to a first light treatment, an organic first metal salt is added to the first mixture, and the second light treatment is continued to be performed to obtain a composite material; wherein the conduction band energy level of the first metal oxide corresponding to the organic first metal salt is 0.2 to 0.4 eV smaller than the conduction band energy level of the n-type metal oxide, the organic first metal salt includes an organic anion and a first metal cation, the range of the organic anion is the same as that described above, and these are not repeated.

[0065] In this embodiment, the first mixture is subjected to a first light irradiation treatment, and under the light irradiation, the n-type metal oxide can excite electrons (e - ), electrons can react with oxygen and water in the first mixture system to generate hydroxide, and after the organic first metal salt is added to the system, the first metal cation in the organic first metal salt can react with the hydroxide to generate the first metal oxide, and continuing the second light treatment can continuously promote the generation of electrons and improve the efficiency of the reaction; wherein, the organic anion in the organic first metal salt can be connected to the surface of the n-type metal oxide, thereby photocatalytically generating the first metal oxide in situ through the n-type metal oxide, thereby improving the binding property of the n-type metal oxide and the first metal oxide and reducing the defects of the n-type metal oxide.

[0066] The reaction mechanism can be referred to as follows:

[0067]

[0068] The first metal oxide formed by the first organic metal salt has a conduction band energy level 0.2 to 0.4 eV lower than that of the n-type metal oxide, thereby reducing the electron injection barrier and improving the electron injection and transport performance of the composite material. The organic anion is connected to the surface of the n-type metal oxide, which can combine with a large number of oxygen defects on the surface of the n-type metal oxide, increase the dispersibility of the n-type metal oxide, and improve the film-forming property of the composite material; on the other hand, it can also improve the electron injection performance of the composite material.

[0069] In addition, during the first light treatment, the holes generated by photocatalysis (h + ) can effectively fill the defects on the surface of n-type metal oxides (such as oxygen vacancies, etc.), play a role in passivating the n-type metal oxides, and can effectively avoid the regrowth of n-type metal oxide nanoparticles.

[0070] In the step S11: the n-type metal oxide can refer to the relevant description in the composite material described above, which will not be repeated here. In one embodiment, the concentration of the n-type metal oxide in the first mixture is 40-60 mg / mL, specifically 45 mg / mL, 50 mg / mL, 55 mg / mL, etc. The first solvent includes one or more of an alcohol solvent, an ether solvent, tetrahydrofuran, acetone, chlorobenzene, toluene, etc. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc.

[0071] In one embodiment, before providing the first mixture, the method further includes: preparing an n-type metal oxide, specifically including the following steps: step S111: dissolving an n-type metal salt in a fourth solvent to obtain an n-type metal salt precursor solution; and dispersing a base in a fifth solvent to obtain an alkaline solution; step S112: adding the alkaline solution to the n-type metal salt precursor solution and stirring to obtain an n-type metal oxide.

[0072] In the step S111: the n-type metal salt is set accordingly according to the specific type of the n-type metal oxide. In a specific embodiment, the n-type metal oxide is zinc oxide, and the n-type metal salt is a zinc salt. Specifically, the zinc salt can be selected from one or more of zinc acetate, zinc chloride, zinc bromide, zinc sulfate, zinc carbonate, zinc phosphate, zinc borate and zinc molybdate. In another specific embodiment, the n-type metal oxide is magnesium-doped zinc oxide, and the n-type metal salt includes a zinc salt and a magnesium salt. The molar ratio of the magnesium salt to the zinc salt can be (0.05-5):100, specifically (0.05-1):100, (1-2):100, (2-3):100, (3-4):100, (4-5):100, etc. In one embodiment, the concentration of the n-type metal salt in the n-type metal salt precursor solution may be 0.15M to 2M, specifically 0.15M to 0.5M, 0.5M to 1M, 1M to 1.5M, 1.5M to 2M, etc. In one embodiment, the fourth solvent may include one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, or diethyl ether. In one embodiment, the concentration of the alkali solution may be 0.08 to 0.2M, specifically 0.08M, 0.1M, 0.125M, 0.15M, 0.18M, ​​etc. In one embodiment, the base can be selected from one or more of potassium hydroxide, lithium hydroxide, sodium hydroxide, ammonium hydroxide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, and tetraalkylammonium hydroxide (TAAOH, alkyl = methyl, ethyl, propyl, butyl); in one embodiment, the fifth solvent can include one or more of methanol, ethanol, propanol, butanol, ethylene glycol, isopropanol, glycerol, etc.

[0073] In the step S112: In one embodiment, an alkali solution is added to the n-type metal salt precursor solution to control the system pH to be 11 to 13. In one embodiment, the stirring time may be 1 to 3 hours, specifically 1 to 1.5 hours, 1.5 to 2 hours, 2 to 2.5 hours, 2.5 to 3 hours, etc. In one embodiment, after the stirring, the mixed system may be precipitated in excess ethyl acetate or acetone, and the supernatant may be removed and centrifuged to obtain the n-type metal oxide.

[0074] In the step S12: Specifically, the organic anion can refer to the related description of the organic group mentioned above, which will not be repeated here.

[0075] Add an organic first metal salt to the first mixture, wherein the mass ratio of the organic first metal salt to the n-type metal oxide is (6-12):100, specifically (6-11):100, (7-11):100, (7-10):100, (8-10):100, (8-8):100, etc. The mass ratio can provide enough of the organic first metal salt to form the first metal oxide, thereby improving the film-forming property of the composite material, making the composite material include a gradient conduction band energy level, thereby reducing the electron injection barrier and improving the electron injection and transport performance of the composite material. The above-mentioned organic anion is electronegative and can be coordinated to the surface of the n-type metal oxide, so that it can combine with a large number of oxygen defects (O2+) on the surface of the n-type metal oxide, increase the dispersibility of the n-type metal oxide, improve the film-forming property of the composite material, and enhance the electron injection performance of the composite material.

[0076] In one embodiment, the first metal cation may include one or more of cobalt ions (Co2+) and molybdenum ions (Mo2+). In a specific embodiment, the organic first metal salt includes an organic cobalt salt, which may specifically include one or more of 2-ethylhexanoic acid cobalt (II), bis (ethylcyclopentadiene) cobalt (II), cyclopentane acid cobalt (II), neodecanoic acid cobalt (II), benzoic acid cobalt (II), etc. Wherein "II" indicates that the valence state of cobalt is 2. In a specific embodiment, the organic first metal salt includes an organic molybdenum salt, which may specifically include 2-ethylhexanoic acid molybdenum, tri (N-butylene-3,5-dimethylaniline) molybdenum, bis (tert-butylimino) bis (dimethylamino) molybdenum, etc. Wherein "II" indicates that the valence state of cobalt is 2. In one embodiment, the first mixture also includes a hole sacrificial agent, which can consume the holes generated by photocatalysis, thereby providing more electrons to generate hydroxide.

[0077] Further, the hole sacrificial agent may include one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, lactic acid, etc. In one embodiment, the mass ratio of the hole sacrificial agent to the n-type metal oxide may be (0.5-1.5):5, specifically (0.5-1.0):5, (1.0-1.5):5, etc. It can be understood that when the first solvent included in the first mixture includes methanol, ethanol, etc., the first solvent may have the function of a hole sacrificial agent and consume holes, and the hole sacrificial agent may not be added additionally.

[0078] In one embodiment, the organic first metal salt is added to the first mixture in the form of a solution. Specifically, the second solvent corresponding to the organic first metal salt may include one or more of water, alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, and toluene. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, and n-butanol. The ether solvent includes one or more of methyl ether and ethyl ether.

[0079] In one embodiment, the first organic metal salt is added while the first mixture is in a stirring state to improve the mixing uniformity of the first mixture and the first organic metal salt, thereby promoting the generation of the first metal oxide.

[0080] The time of the first light treatment is 1 to 2 hours, specifically 1, 1.5 hours, 2 hours, etc. In one embodiment, the first light treatment is full-spectrum light treatment, that is, full-band irradiation is adopted. In one embodiment, the wavelength range of the first light treatment is 200 to 2500nm, such as one or more of 380nm, 760nm, etc. In one embodiment, the first light treatment may include one or more of the ultraviolet light band (UV for short, wavelength 200 to 380nm), the visible light band (VL for short, wavelength 380 to 760nm) or the infrared light band (IR for short, wavelength 760 to 2500nm). In one embodiment, the light source of the first light treatment may be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the first light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp may be 200 to 500W, such as 300W, 400W, 500W, etc. In one embodiment, during the first light treatment, the first mixture is in a stirring state to improve mixing uniformity, improve light uniformity, and improve heat dissipation. In one embodiment, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0 to 30°C, such as 0 to 4°C, 4 to 20°C, 20 to 25°C, 25 to 30°C, etc. Specifically, the first mixture can be protected by circulating condensed water to control the temperature of the first mixture within a preset range to avoid excessive temperature of the first mixture due to heat generation from light.

[0081] The time of the second light treatment is 4 to 10 hours, specifically 5 to 9 hours, 6 to 9 hours, 6 to 8 hours, 7 to 8 hours, etc. In one embodiment, the second light treatment is full-spectrum light treatment, that is, full-band irradiation is adopted. In one embodiment, the wavelength range of the second light treatment is 200 to 2500nm, such as one or more of 380nm, 760nm, etc. In one embodiment, the second light treatment may include one or more of the ultraviolet light band (UV for short, wavelength 200 to 380nm), the visible light band (VL for short, wavelength 380 to 760nm) or the infrared light band (IR for short, wavelength 760 to 2500nm). In one embodiment, the light source of the second light treatment may be a single light source or a composite light source formed by multiple light sources. In a specific embodiment, the light source of the second light treatment is a xenon (Xe) lamp. Specifically, the power of the Xe lamp may be 200 to 500W, such as 300W, 400W, etc.

[0082] In one embodiment, an organic first metal salt is added to the first mixture to obtain a second mixture, and a second light treatment is continued. During the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0 to 30°C, such as 0 to 4°C, 4 to 20°C, 20 to 25°C, 25 to 30°C, etc. Specifically, the second mixture can be protected by circulating condensed water to control the temperature of the second mixture within a preset range to avoid excessive temperature of the second mixture due to heat generation from light. In one embodiment, an organic first metal salt is added to the first mixture to obtain a second mixture, and during the second light treatment, the second mixture can be in a stirring state to improve mixing uniformity and increase the generation rate of the first metal oxide.

[0083] In one embodiment, after the second light treatment, the method further includes: using a cleaning agent to perform sedimentation washing on the mixture N times, where N is an integer greater than or equal to 2, such as washing three times. The cleaning agent may include one or more of ethyl acetate and acetone. In this embodiment, unreacted reactants, such as unreacted organic first metal salt, etc., may be removed by multiple washings.

[0084] The present application provides a light emitting device, referring to Figure 2 , Figure 2 The present application provides a structural schematic diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 that are relatively arranged, and a light-emitting layer 30 that is arranged between the first electrode 10 and the second electrode 20, and an electronic functional layer 40 that is arranged between the second electrode 20 and the light-emitting layer 30.

[0085] Wherein, the material of the electronic functional layer 40 includes the composite material provided in the present application, or includes the composite material obtained by the preparation method of the composite material provided in the present application. In the present embodiment, the material of the electronic functional layer 40 includes a composite material, that is, an n-type metal oxide doped with a first metal oxide, wherein the conduction band energy level of the first metal oxide is 0.2 to 0.4 eV less than the conduction band energy level of the n-type metal oxide, and an energy level gradient with gradually decreasing energy levels is formed between the n-type metal oxide, the first metal oxide and the second electrode 20. In other words, an intermediate energy level is introduced between the n-type metal oxide and the second electrode 20 through the first metal oxide, thereby facilitating the reduction of the electron injection barrier and improving the electron injection of the light-emitting device 100.

[0086] In this embodiment, the organic group is coordinated and connected to the surface of the n-type metal oxide, which can be connected to the large number of oxygen defects (O 2+ ) can increase the dispersibility of the n-type metal oxide and improve the film-forming property of the composite material, thereby improving the uniformity and density of the film of the electronic functional layer 40, reducing and avoiding the leakage current phenomenon of the light-emitting device 100, and improving the stability of the light-emitting device 100; on the other hand, the organic group can further enhance the injection of electrons in the light-emitting device 100.

[0087] In addition, the organic group coordinated and connected to the surface of the n-type metal oxide can also isolate the direct contact between the n-type metal oxide and the electrode to a certain extent, avoiding the instability of the efficiency and other performance of the light-emitting device 100 caused by the contact reaction between the n-type metal oxide and the electrode, thereby improving the stability of the light-emitting device 100 during storage or storage.

[0088] In one embodiment, the material of the electronic functional layer 40 is composed of a composite material. In other embodiments, the material of the electronic functional layer 40 may include other materials such as metal elements in addition to the composite material. In one embodiment, the electronic functional layer 40 may include one or both of an electron injection layer 41 and / or an electron transport layer 42; when the electronic functional layer 40 includes the electron injection layer 41 and the electron transport layer 42, the electron injection layer 41 is arranged close to the second electrode 20, and the electron transport layer 42 is arranged close to the light-emitting layer 30, and the material of the electron transport layer 42 includes the composite material.

[0089] In one embodiment, the thickness of the electron transport layer 42 may be 20-40 nm, specifically 20 nm, 25 nm, 35 nm, 40 nm, etc. In one embodiment, the material of the electron injection layer 41 may be a material known in the art for electron injection layer, for example, may be selected from but not limited to LiF, MgP, MgF2 、Al 2 O 3 , Ga 2 O 3 、LiF / Yb、ZnO、Cs 2 CO 3 , RbBr, Rb 2 CO 3 At least one of .

[0090] In one embodiment, the material of the light-emitting layer 30 is selected from an organic light-emitting material or a quantum dot light-emitting material. The organic light-emitting material can be selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light; the quantum dot light-emitting material can be selected from at least one of single-structure quantum dots, core-shell structure quantum dots, and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds, and I-III-VI compounds, and the II-VI compounds are selected from CdS, CdS e. CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnT e. CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnS The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe; the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, and GaPAs , at least one of GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS;The core of the quantum dots with a core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots with a core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;

[0091] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX 3 , where A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX 3 , wherein B is an organic amine cation selected from CH 3 (CH 2 ) n-2 NH 3 + or [NH 3 (CH 2 ) n NH 3 ] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I -When n=2, the inorganic metal halide octahedral MX 6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX connected in a top-sharing manner 6 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.

[0092] In one embodiment, the quantum dot luminescent material includes one or more of red quantum dots, green quantum dots, and blue quantum dots. The thickness of the luminescent layer 30 may be 5 to 100 nm, specifically 5 to 15 nm, 15 to 30 nm, 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, 30 to 50 nm, 50 to 100 nm, etc.

[0093] In a specific embodiment, the quantum dots are selected from oily quantum dots, and the surface of the quantum dots is connected with a ligand that is easily soluble in a solvent with low polarity, including at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. As a specific embodiment, the acid ligand is at least one of decadecanoic acid, undecylenic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand is at least one of octanethiol, dodecylthiol, and octadecylthiol; the amine ligand includes at least one of oleylamine, octadecylamine, and octaamine; the (oxygen) phosphine ligand is at least one of trioctylphosphine and trioctylphosphine oxide.

[0094] In one embodiment, the light emitting device 100 may further include a hole functional layer 50, and the hole functional layer 50 is disposed between the first electrode 10 and the light emitting layer 30. The hole functional layer 50 may include a hole injection layer 51 and / or a hole transport layer 52. When the hole functional layer 50 includes two layers, the hole injection layer 51 and the hole transport layer 52, the hole injection layer 51 is disposed close to the first electrode 10, and the hole transport layer 52 is disposed close to the light emitting layer 30. In one embodiment, the thickness of the hole injection layer 51 may be 20 to 200 nm, specifically 20 nm, 80 nm, 120 nm, 150 nm, etc. The thickness of the hole transport layer 52 may be 30 to 180 nm, specifically 30 nm, 50 nm, 80 nm, 120 nm, 150 nm, etc.

[0095] The material of the hole transport layer 52 is selected from arylamine, polyaniline, polypyrrole, poly(p-phenylene vinylene) and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO 3 , WO 3 、V 2 O 5 CrO 3 , CuO, MoS 2 、MoSe 2 , WS 3 ,WSe 3 , CuS, CuSCN; wherein the aromatic amine is selected from 4,4'-bis(9-carbazole)biphenyl (CBP), poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenyl benzidine (DNTPD), poly (9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4',4"-tris(carbazol-9-yl)triphenylamine (TCATA), 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), 4,4',4"-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), N,N'-diphenyl-N,N'-bis( 1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis( The invention relates to a poly(p-phenylene vinylene) and a poly(p-phenylene vinylene) derivative selected from one or more of poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV).

[0096] The material of the hole injection layer 51 is a material having hole injection capability, selected from poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NP-4- ... D), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tris(diphenylamino)triphenylamine doped with F4-TCNQ (TDATA), p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), transition metal oxides, and transition metal sulfide compounds; wherein the transition metal oxides include NiO, MoO 2 , WO 3 , CuO; the metal sulfide compound includes MoS 2 、MoSe 2 , WS 3 ,WSe 3 , CuS or more.

[0097] In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZO, ICO, AMO, SnO 2 、In 2 O 3 、Cd:ZnO、F:SnO 2 、In:SnO 2 、Ga:SnO2 At least one of the following; the material of the composite electrode is selected from AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO 2 / Ag / TiO 2 、TiO 2 / Al / TiO 2 At least one of ZnS / Ag / ZnS and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three layers stacked together consisting of an AZO layer, an Ag layer and an AZO layer. The first electrode 10 and the second electrode 20 are a pair of electrodes. In one embodiment, the first electrode 10 is an anode, and the second electrode 20 is a cathode.

[0098] It can be understood that, in addition to the above-mentioned functional layers, the light-emitting device 100 can also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer. It can be understood that the materials and thicknesses of the various layers of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100. The light-emitting device 100 also includes a substrate (not shown), which can also be called a substrate. The substrate can be a rigid substrate or a flexible substrate. The rigid substrate can be a ceramic material or various glass materials. The flexible substrate can be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.

[0099] It can be understood that the light-emitting device 100 can be an upright light-emitting device or an inverted light-emitting device. When the light-emitting device 100 is an upright light-emitting device, the substrate is combined with the side of the first electrode 10 away from the light-emitting layer 30. When the light-emitting device 100 is an inverted light-emitting device, the substrate is combined with the side of the second electrode 20 away from the light-emitting layer 30. It can be understood that in addition to the above-mentioned functional layers, the light-emitting device 100 can also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer. It can be understood that the materials and thicknesses of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100.

[0100] The present application also provides a method for preparing a light emitting device, see Figure 3 , Figure 3 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:

[0101] Step S21: providing a preset device, wherein the preset device includes a first electrode and a light-emitting layer;

[0102] Step S22: Arranging electronic functional materials on the preset device to form an electronic functional layer;

[0103] Step S23: forming a second electrode on the electronic functional layer to obtain a light-emitting device.

[0104] The light-emitting device prepared in this embodiment is an upright device.

[0105] In one embodiment, the light-emitting device includes a hole functional layer, and the step S21 specifically includes: providing a prefabricated device, wherein the prefabricated device includes a stacked first electrode, a hole functional layer, and a light-emitting layer.

[0106] See also Figure 4 , Figure 4 This is a flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application. The method for preparing a light-emitting device in this embodiment comprises the following steps:

[0107] Step S31: providing a prefabricated device, wherein the prefabricated device includes a stacked second electrode;

[0108] Step S32: Arranging electronic functional materials on the prefabricated device to form an electronic functional layer;

[0109] Step S33: forming a stacked light-emitting layer and a first electrode on the electronic functional layer to obtain a light-emitting device.

[0110] The light-emitting device prepared in this embodiment is an inverted device.

[0111] In one embodiment, the light-emitting device includes a hole functional layer, and the step S33 specifically includes: forming a stacked light-emitting layer, a hole functional layer and a first electrode on the electronic functional layer.

[0112] In the above two embodiments, the electronic functional material includes the composite material provided in the present application, or includes a composite material obtained by the preparation method of the composite material provided in the present application. For details, please refer to the relevant description above, which will not be repeated here. In a specific embodiment, the electronic functional material is the composite material provided in the present application, or a composite material obtained by the preparation method of the composite material provided in the present application. In one embodiment, in step S22 and step S32, the composite material can be set on the prefabricated device by a solution method. Specifically, the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip pulling, immersion, spraying, roller coating, casting, slit coating and strip coating, etc.

[0113] In a specific embodiment, in step S22 and step S32, the composite material is arranged on the preset device to form an electronic functional layer, including: a third mixture is arranged on the preset device, wherein the third mixture includes the composite material and a third solvent. Specifically, the third solvent may include an alcohol solvent, specifically one or more of methanol, ethanol, isopropanol, n-butanol, etc. Further, in an embodiment, the concentration of the electronic functional material in the third mixture may be 20 to 50 mg / mL, specifically 20 mg / mL, 25 mg / mL, 30 mg / mL, 40 mg / mL, etc.

[0114] After the third mixture is prepared by the solution method, it is necessary to dry it to remove the third solvent. The drying can be heating drying or vacuum drying, wherein the heating drying temperature can be 60 to 80°C and the time can be 20 to 60 minutes. The vacuum drying, the vacuum drying pressure is 10 -1 ~10 -2 Pa. Furthermore, the vacuum drying temperature may be room temperature (about 25° C.).

[0115] In other embodiments, the composite material may be disposed on the prefabricated device by other methods known in the art, such as sputtering, etc. In each embodiment of the above-mentioned preparation method, the electron transport layer, the hole functional layer, the light-emitting layer, the first electrode, the second electrode, etc. may refer to the corresponding description in the light-emitting device 100 in the above text, and will not be described in detail here.

[0116] In the light-emitting device provided in the present application, the preparation methods of the first electrode, the second electrode, the light-emitting layer, the hole functional layer, the electron functional layer and other film layers can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.

[0117] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.

[0118] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0119] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0120] Embodiment 1:

[0121] This embodiment provides a method for preparing a composite material and the prepared composite material, wherein the preparation method specifically comprises the following steps:

[0122] Step 1: Dissolve zinc acetate in dimethyl sulfoxide to obtain a 0.18 M metal salt precursor solution; disperse potassium hydroxide in ethanol to obtain a 0.2 M alkali solution.

[0123] Step 2: adding alkaline solution to the metal salt precursor solution, stirring for 2 hours, settling the mixture in excess ethyl acetate or acetone, removing the supernatant and centrifuging, dispersing in an ethanol solution to obtain an ethanol solution of zinc oxide nanoparticles.

[0124] Step 3: Take 20 mL of the 40 mg / mL zinc oxide ethanol solution and irradiate the solution under a 300 W Xe lamp (full spectrum) for 1 hour under the protection of circulating condensed water at 4°C while continuously stirring.

[0125] Step 4: Under continuous illumination, 15 mL of 3.5 mg / mL 2-ethylhexanoate cobalt (II) ethanol solution was added dropwise to the solution in step 3, and the illumination was continued for 6 hours, during which the solution was protected by circulating condensed water at 4°C. After photodeposition, the solution was washed three times by precipitation in excess ethyl acetate or acetone to wash away excess copper salt and obtain a composite material.

[0126] Embodiment 2:

[0127] This example is substantially the same as Example 1, except that in step 4, 15 mL of 4.5 mg / mL 2-ethylhexanoate cobalt (II) ethanol solution is added.

[0128] Embodiment 3:

[0129] This example is substantially the same as Example 1, except that in step 4, 15 mL of 6.0 mg / mL 2-ethylhexanoate cobalt (II) ethanol solution is added.

[0130] Embodiment 4:

[0131] This example is substantially the same as Example 1, except that in step 4, 15 mL of 5.0 mg / mL bis(ethylcyclopentadienyl)cobalt(II) ethanol solution is added.

[0132] Embodiment 5:

[0133] This example is substantially the same as Example 1, except that in step 4, 15 mL of a 5.0 mg / mL ethanol solution of cobalt (II) cyclohexaneate is added.

[0134] Embodiment 6:

[0135] This example is substantially the same as Example 1, except that in step 4, 15 mL of 5.0 mg / mL neodecanoate cobalt (II) ethanol solution is added.

[0136] Embodiment 7:

[0137] This example is substantially the same as Example 1, except that in step 4, 15 mL of a 5.0 mg / mL cobalt (II) benzoate ethanol solution was added, and irradiation was continued for 8 hours.

[0138] Embodiment 8:

[0139] This example is substantially the same as Example 1, except that in step 4, 15 mL of a 3.2 mg / mL bis(ethylcyclopentadienyl)cobalt(II) ethanol solution and 15 mL of a 1.5 mg / mL neodecanoate cobalt(II) ethanol solution were added, and irradiation was continued for 10 hours.

[0140] Embodiment 9:

[0141] This example is substantially the same as Example 1, except that in step 4, 15 mL of a 3.2 mg / mL bis(ethylcyclopentadienyl)cobalt(II) ethanol solution and 15 mL of a 1.5 mg / mL cobalt(II) benzoate ethanol solution were added.

[0142] Embodiment 10:

[0143] This example is substantially the same as Example 1, except that in step 4, 15 mL of 1.5 mg / mL 2-ethylhexanoate cobalt (II) ethanol solution is added.

[0144] Embodiment 11:

[0145] This example is substantially the same as Example 1, except that in step 4, 15 mL of a 10 mg / mL 2-ethylhexanoate cobalt (II) ethanol solution is added.

[0146] Example 12

[0147] The present embodiment is substantially the same as Example 1, except that: in step 4, 15 mL of 5.0 mg / mL 2-ethylhexanoic acid platinum ethanol solution is added.

[0148] Comparative Example 1:

[0149] This embodiment is basically the same as embodiment 1, except that step 3 and subsequent steps are not performed, and zinc oxide nanoparticles are obtained in step 2.

[0150] Comparative Example 2:

[0151] This embodiment is basically the same as embodiment 1, except that: Step 4 is: adding 15 mL of 5.0 mg / mL cobalt oxide-ethanol solution, stirring the solution for 6 hours, and then washing the solution three times by precipitation in excess ethyl acetate or acetone to obtain a zinc oxide-cobalt oxide mixed material.

[0152] The preparation method of cobalt oxide is as follows: dispersing an appropriate amount of cobalt chloride in 25 mL of ethanol to form a cobalt chloride solution with a concentration of 1 mol / L, dissolving an appropriate amount of sodium hydroxide in 5 mL of ethanol to prepare a sodium hydroxide solution with a concentration of 1 mol / L, and adding the sodium hydroxide solution dropwise to the cobalt chloride solution until the cobalt ion: OH - The molar ratio of is 1:1.7 to form a mixed system with a pH of 13, and then the mixed system is heat-treated under stirring at a temperature of 60°C and a time of 3 hours to obtain a cobalt oxide solution.

[0153] Comparative Example 3:

[0154] This embodiment is basically the same as embodiment 1, except that: Step 4 is: adding 15 mL of 5.0 mg / mL molybdenum oxide-ethanol solution, stirring the solution for 6 hours, and then washing the solution three times by precipitation in excess ethyl acetate or acetone to obtain a zinc oxide-molybdenum oxide mixed material.

[0155] The preparation method of molybdenum oxide is as follows: 10 mmol of ammonium molybdate and 300 mmol of thiourea are added to 350 ml of deionized water, reacted in a reactor at 110° C. for 2 hours, and finally filtered with a 0.22 μm microporous filter membrane to obtain a molybdenum oxide ethanol solution.

[0156] Device Example 1

[0157] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.

[0158] Step 1: Place the ITO glass sheet in a glass dish filled with ethanol solution, and ultrasonicate with acetone, deionized water, and ethanol for 20 minutes respectively, and then blow dry with a nitrogen gun; then place the cleaned ITO glass sheet in oxygen plasma for further cleaning for 10 minutes; continue to use UV-ozone to treat the surface of the ITO substrate for 15 minutes;

[0159] Step 2: Spin-coat the cleaned ITO glass sheet with PEDOT:PSS (thickness of about 25 nm) in air at a speed of 3500 r / min for 30 seconds; after spin coating, place it in air for annealing at 150°C for 30 minutes to obtain a hole injection layer; after annealing, quickly transfer the sheet to a glove box in a nitrogen atmosphere;

[0160] Step 3: Continue to spin-coat TFB (8 mg / mL, chlorobenzene solution) on the glass / ITO / PEDOT:PSS device at a speed of 3000 r / min for 30 seconds; after the spin coating is completed, anneal in a glove box at a temperature of 180°C for 30 minutes to obtain a hole transport layer with a thickness of 30 nm;

[0161] Step 4: CdZnSe / ZnSe / Cd 0.6 ZnS 2 / ZnSe blue quantum dots were spin-coated on the hole transport layer at a spin-coating speed of 2000 r / min for 30 seconds; after the spin-coating was completed, the layers were annealed at 60 degrees Celsius in a glove box for 5 minutes to obtain a light-emitting layer;

[0162] Step 5: The composite material in Example 1 is formed into a composite material ethanol solution with a concentration of 30 mg / mL, and spin-coated on the light-emitting layer at a speed of 3000 r / min for 30 seconds, and dried to obtain an electron transport layer with a thickness of 30 nm.

[0163] Step 6: Place the sample prepared in step 5 into a vacuum chamber, evaporate a top silver electrode with a thickness of 100 nm, and encapsulate.

[0164] Device Examples 2-12

[0165] Device Examples 2-12 are substantially the same as Device Example 1, with the only difference being that in step 5, the composite materials of Examples 2-12 are used respectively.

[0166] Device Comparison Examples 1-3

[0167] Device comparison examples 1-3 are basically the same as device embodiment 1, and the only differences are: the ZnO-ethanol solution in comparison example 1 is directly used in step 5, the zinc oxide-cobalt oxide mixed material in comparison example 2 is used in step 5, and the zinc oxide-molybdenum oxide mixed material in comparison example 3 is used in step 5.

[0168] Test 1:

[0169] The external quantum efficiency of the quantum dot light-emitting diodes of device examples 1-12 and device comparative examples 1-2 was tested, and the data is shown in Table 1. Figure 5 EQE-J curves (i.e., external quantum efficiency-current density curves) of device examples 1-11 and device comparative examples 1-2, Figure 6 The external quantum efficiency stability curves of device embodiments 2 and 4 and device comparative example 1 are shown.

[0170] Among them, the detection method of external quantum efficiency EQE is: the ratio of the number of electron-hole pairs injected into quantum dots to the number of emitted photons, the unit is %, which is an important parameter to measure the quality of electroluminescent devices, and can be obtained by measuring with EQE optical testing instruments. The specific calculation formula is as follows:

[0171]

[0172] Among them, ηe is the light output coupling efficiency, ηγ is the ratio of the number of recombined carriers to the number of injected carriers, x is the ratio of the number of excitons that generate photons to the total number of excitons, and K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0173] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0174] Test 2:

[0175] The single electron devices (EOD) corresponding to device embodiments 1-11 and device comparative examples 1-2 were tested for electron injection performance, and the data of the corresponding EOD device current density and EOD device operating voltage are shown in Table 1. Figure 7 : is the JV curve (i.e., current density-voltage curve) of the single electron device corresponding to device examples 1-11 and device comparative examples 1-2, Figure 8 1-1 is the operating voltage curve of the single electron device corresponding to device examples 1-11 and device comparison examples 1-2.

[0176] Among them, the preparation method of the single electron device (EOD) is basically the same as the preparation method of the corresponding complete QLED device. The only difference is that the hole injection layer and the hole transport layer are subtracted, and the device structure is: glass substrate / ITO / QD light-emitting layer / electron transport layer / Ag electrode.

[0177] The electron injection performance test method is: control QE PRO and Keithley 2400 through LabView to build a QLED efficiency test system. The system tests the current density-voltage curve of the single carrier transport thin film device (EOD). The current density under the working voltage (8V) of the device is compared with the working voltage in the stable state. The working voltage in the stable state refers to the working voltage of the device in the device balance stage when the device runs for more than 4 hours during the device life test.

[0178] Table 1

[0179]

[0180] From Table 1 and Figure 5 , 7 -8 It can be seen that, compared with device comparison examples 1 and 2, the current density of the EOD device (at 8V) of each device embodiment is improved, and the corresponding operating voltage of the EOD device is significantly reduced. This shows that the strategy of this solution can achieve the purpose of improving the electron injection of the QLED light-emitting device. Ultimately, the efficiency of the QLED device is greatly improved.

[0181] From the comparison of Comparative Example 2 and other embodiments, it can be found that directly mixing nano cobalt oxide and nano zinc oxide together does not show obvious beneficial effects. It can be seen that the cobalt oxide material generated in situ on the surface of the zinc oxide material in the present application has a closer contact between the two and more effectively realizes the injection of electrons. At the same time, the introduction of organic groups can have an electron-donating effect, which can also achieve the effect of enhancing electron injection.

[0182] It can be seen from device embodiments 1-3 and 10-11 that the electron injection enhancement effect of device embodiments 10 and 11 is relatively small. This may be because a small amount of organic cobalt salt is added, resulting in a small amount of cobalt oxide contained in the composite material, and thus the enhancement effect on point injection is relatively small; while a large amount of organic cobalt salt is added, resulting in a large amount of cobalt oxide contained in the composite material, which leads to excessive electron injection of the device, resulting in a decrease in the external quantum efficiency of the device.

[0183] Figure 6 The external quantum efficiency stability curves of the quantum dot light emitting diodes of device examples 2 and 4 and device comparative example 1 are shown. Figure 6 It can be seen that compared with device comparative example 1, the stability of the external quantum efficiency of device embodiments 2 and 4 during storage or storage is significantly improved. After 60 days of storage, the EQE value of device embodiment 2 only decreased by 8.91%, while that of comparative example 1 decreased by 52.57%. This may be due to the fact that in the process of photocatalytic in-situ generation of cobalt oxide to obtain the composite material, the holes generated by photocatalysis consume part of the hydroxyl groups on the surface of the zinc oxide nanoparticles, thereby effectively reducing the interaction between the hydroxyl groups and the cathode electrode, and the presence of the organic ligand can also isolate the direct contact between the zinc oxide nanoparticles and the electrode to a certain extent, thereby improving the storage stability of the device.

[0184] Test 3:

[0185] In the process of preparing the quantum dot light-emitting diodes of device example 2 and device comparative example 1, after preparing the electron transport layer, an AFM (atomic force microscope) roughness test was performed on the electron transport layer, and the roughness of the electron transport layer was obtained. Fig. 9 and Fig.10 , Fig. 9 and Fig.10 The AFM images of the electron transport layer in device comparative example 1 and device embodiment 2 respectively correspond to each other.

[0186] The root mean square roughness of the electron transport layer in device Example 2 (Rq 1.70nm) is much smaller than that of the device comparative example 1 (Rq 2.51nm), indicating that the electron transport layer formed by the composite material provided in the present application has good film-forming property and surface uniformity. The composite material provided has good film-forming property, which may be due to the fact that the organic anions are connected to the surface of the n-type metal oxide and can react with a large number of oxygen defects (O2+ ) and effectively reduce the aggregation and regrowth of zinc oxide particles, thereby improving the film-forming property of the composite material. It is also possible that during the preparation of the composite material, the holes (h+) generated by photocatalysis can effectively fill the defects (such as oxygen vacancies, etc.) on the surface of the n-type metal oxide, play a role in passivating the n-type metal oxide, and can effectively avoid the regrowth of n-type metal oxide nanoparticles, improve the uniformity of the particles in the composite material, reduce agglomeration, and thus also improve the film-forming property of the composite material.

[0187] Test 4:

[0188] The zinc oxide-ethanol solution of Comparative Example 1 and the composite material-ethanol solution of Example 2 were tested for hydrated particle size using a laser particle size analyzer to obtain a hydrated particle size distribution diagram. Fig.11 and Fig.12 The hydrated particle size distribution diagrams of the composite materials corresponding to Example 1 and Example 2 respectively.

[0189] Depend on Fig.11 and Fig.12 It can be seen that the average particle size of the single nano zinc oxide in Comparative Example 1 is 4.37 nm, and the average particle size of the composite material formed in Example 2 is 3.01 nm, and the particle size distribution is more concentrated, the particle size distribution is more uniform, and the particles are smaller. It may be that in the process of photocatalytic in-situ generation of cobalt oxide to obtain the composite material, the holes generated by photocatalysis can effectively fill the defects on the surface of the zinc oxide material (such as oxygen vacancies, etc.), play a role in passivating the zinc oxide material, and the organic anions are connected to the surface of the n-type metal oxide, which can react with a large number of oxygen defects (O 2+ ) can effectively avoid the regrowth of zinc oxide nanoparticles and reduce agglomeration, so that the particles of the composite material are smaller and more evenly distributed.

[0190] Test 5:

[0191] The conduction band positions of zinc oxide in Example 1 and cobalt oxide prepared in Comparative Example 2 were measured by Mott-Schottky. Specifically, the measurement was performed on a Zennium E electrochemical workstation (zhner, Germany) at test frequencies of 500 Hz, 1 kHz, and 1.5 kHz (three frequencies to improve accuracy), an amplitude of 10 mV, and a standard three-electrode quartz cell containing 0.5 M Na 2 SO 4 Electrolyte solution, platinum wire as counter electrode, Hg / Hg in saturated KCl 2+ As a reference electrode, an ITO glass substrate was pre-coated with a test sample film (coating area of ​​1 cm 2 , the thin film preparation method is the same as the device film preparation method) as the working electrode. Fig.13 and Fig.14 Conduction band position diagrams of zinc oxide and cobalt oxide respectively.

[0192] Combination Fig.13 and Fig.14 It can be seen that the conduction band position of zinc oxide is at -0.22eV, and the conduction band position of cobalt oxide is at -0.08eV. A composite material formed by cobalt oxide is in situ generated in zinc oxide. By introducing cobalt oxide of intermediate energy level between zinc oxide and the cathode electrode, an energy level gradient is formed between zinc oxide and the cathode electrode, thereby improving the electron injection of the device and improving the luminescence efficiency of the device.

[0193] The composite materials and their preparation methods, light-emitting devices and their preparation methods, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite material, characterized in that: An n-type metal oxide doped with a first metal oxide, wherein a negatively charged organic group is connected to the surface of the n-type metal oxide, wherein the organic group comprises one or more of the following structures: Wherein, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; R2 and R5 are selected from one or more combinations of H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, C3-C10 cycloalkyl; n is an integer of 0-4, and m is an integer of 0-6.

2. The composite material according to claim 1, characterized in that Each occurrence of R1, R2, R3, R4, and R5 is independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C10 alkyl, substituted or unsubstituted C3-C10 cycloalkyl, substituted or unsubstituted C2-C10 alkenyl, substituted or unsubstituted C3-C10 cycloalkenyl, substituted or unsubstituted aryl having 6-12 ring atoms, and substituted or unsubstituted heteroaryl having 5-12 ring atoms; Wherein, the substituent is selected from one or more combinations of C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, and C3-C10 cycloalkyl.

3. The composite material according to claim 2, characterized in that The organic group includes one or more of the following structural formulas:

4. The composite material according to any one of claims 1 to 3, characterized in that The conduction band energy level of the first metal oxide is 0.2 to 0.4 eV smaller than the conduction band energy level of the n-type metal oxide; And / or, the n-type metal oxide includes a doped or undoped second metal oxide, the undoped second metal oxide includes one or more of zinc oxide, titanium dioxide, tin dioxide, and aluminum oxide, the doped second metal oxide includes the undoped second metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y; And / or, the first metal oxide includes one or more of cobalt oxide and molybdenum oxide; and / or, the average particle size of the n-type metal oxide is in the range of 2 to 10 nm; and / or, the average particle size of the first metal oxide is in the range of 2 to 10 nm; And / or, the mass ratio of the first metal oxide to the n-type metal oxide is (3-10):

100.

5. A method for preparing a composite material, characterized in that: include: Providing a first mixture, wherein the first mixture includes an n-type metal oxide and a first solvent, wherein the first solvent includes a hole sacrificial agent; After the first mixture is subjected to a first light treatment, an organic first metal salt is added to the first mixture, and the first mixture is subjected to a second light treatment to obtain a composite material; Wherein, the organic first metal salt includes an organic anion and a first metal cation, and the organic anion includes one or more of the following structures: Wherein, R1, R3, and R4 are independently selected from one or more combinations of H, D, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 6-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; R2 and R5 are selected from one or more combinations of H, D, halogen, nitro, cyano, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted C1-C30 alkoxy, substituted or unsubstituted C1-C30 alkylthio, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C3-C30 cycloalkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C6-C30 cycloalkynyl, substituted or unsubstituted aryl having 5-30 ring atoms, and substituted or unsubstituted heteroaryl having 5-30 ring atoms; The substituent is selected from one or more combinations of halogen, nitro, cyano, carboxyl, hydroxyl, C1-C10 alkoxycarbonyl, C1-C10 chain alkyl, C3-C10 cycloalkyl; n is an integer of 0-4, and m is an integer of 0-6.

6. The preparation method according to claim 5, characterized in that: The conduction band energy level of the first metal oxide corresponding to the first organic metal salt is 0.2 to 0.4 eV smaller than the conduction band energy level of the n-type metal oxide; And / or, the n-type metal oxide includes a doped or undoped second metal oxide, the undoped second metal oxide includes one or more of zinc oxide, titanium dioxide, tin dioxide, and aluminum oxide, the doped second metal oxide includes the undoped second metal oxide and a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y; and / or, the mass ratio of the first organic metal salt to the n-type metal oxide is (6-12):100; And / or, the hole sacrificial agent includes one or more of acetonitrile, triethylamine, triethanolamine, sodium sulfite, methanol, ethanol, and lactic acid; And / or, the first metal cation includes one or more of cobalt ions and molybdenum ions; And / or, the first solvent includes one or more of alcohol solvents, ether solvents, tetrahydrofuran, acetone, chlorobenzene, and toluene.

7. The preparation method according to claim 5, characterized in that: The first light treatment adopts full spectrum irradiation; And / or, the first light treatment lasts for 1 to 2 hours; and / or, during the first light treatment of the first mixture, the temperature of the first mixture is maintained at 0-30° C.; and / or, during the first light irradiation process, the first mixture is in a stirring state; And / or, the second light treatment uses full spectrum irradiation; And / or, the second light treatment time is 4 to 10 hours; And / or, after adding the first organic metal salt to the first mixture, a second mixture is obtained, and during the second light treatment of the second mixture, the temperature of the second mixture is maintained at 0-30° C. and the second mixture is in a stirring state.

8. A light emitting device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; A light-emitting layer is disposed between the first electrode and the second electrode; An electronic functional layer, disposed between the second electrode and the light-emitting layer; Wherein, the material of the electronic functional layer includes the composite material as described in any one of claims 1 to 4, or includes the composite material prepared by the preparation method of the composite material as described in any one of claims 5 to 8.

9. The light emitting device according to claim 8, characterized in that: The material of the light-emitting layer is selected from organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II-V Group I compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnS The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, G at least one of aPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the Group I-III-VI compound is selected from at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2 + Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - , I- at least one; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; And / or, the first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, IT At least one of ZO, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; And / or, the light-emitting device further comprises a hole functional layer, the hole functional layer is arranged between the first electrode and the light-emitting layer, and the hole functional layer comprises a hole injection layer and / or a hole transport layer; wherein the material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9 -octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN or one or more thereof; wherein the aromatic amine is selected from 4,4'-bis(9-carbazole)biphenyl, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)diphenylamine), N,N'-bis(4-(N,N'-diphenyl-amino) triphenylamine, 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, -diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine, 4,4' ,4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, and CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, and CuS.; 10. A display device, characterized in that: The light emitting device comprises the light emitting device as claimed in any one of claims 8 to 9.